ANALISIS PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA DOSEN DI INFORMATICS AND BUSINESS INSTITUTE DARMAJAYA - wibasuri, anggalia (Jurnal Manajemen dan Keuangan, 2011)
The research was conducted to determine the effect of compensation on the performance of lecturers in Informatics and Business Institute Darmajaya. The hypothesis proposed in this study is the compensation effect on the performance of lecturers. The experiment was conducted in the environment Darmajaya Informatics and Business Institute. The number of samples is 79 respondents. Data collection techniques using direct interviews with a questionnaire listing guidelines. The analysis technique used is the classic asusmsi test, whereas hypothesis testing using binary regression analysis. Based on the results of multiple regression analysis of binary, it can be concluded that the financial compensation variables with regression coefficient of 0.001 with significance level of 0.277, at 95% statistically significant effect on the performance of lecturers and Business Informatics Institute Darmajaya. Variable non-financial compensation with the regression coefficient of 0.809 with significance level of 0.035, at 95% confidence level was not statistically affect the performance of lecturers and Business Informatics Institute Darmajaya.Keyword : Non-financial compensation, financial compensation, performance of lecturers.